Categorical Stigma and Firm Disengagement: Nuclear Power Generation in the United States, 1970–2000 - Piazza, Alessandro; Perretti, Fabrizio (Organization Science, 2015)
How do organizations react to stakeholder disapproval of a category to which they belong? In this paper, we draw on the categorization, stigma, and identity literatures in building a theory to predict whether firms that are involved in stigmatized activities will choose to reduce or terminate their involvement in them, as opposed to resorting to less drastic measures such as defensive practice adoption or impression management techniques. Conceptualizing groups of organizations involved in such contentious practices as stigmatized categories in the eyes of an audience, we argue that organizational responses rest on three elements: (1) the intensity of stigma targeting the category, (2) the media exposure of the category, and (3) the extent to which an organization is a member of the category. A quantitative study of proposed new nuclear reactor units in the United States between 1970 and 2000, in the face of mounting opposition to atomic power, provides empirical support for our claims.